Analisis Anuitas Biasa dan Anuitas Jatuh Tempo pada Kredit Motor Jenis Sporty/Fashion dengan Menggunakan Metode Bunga Flat dan Efektif - Nicu Rahmat Adil; Danil Danil; Hafiz, Muhammad Al; Khoirun Laili Nur Amaliah; Akbar, Hadissyah; Humairah, Reni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
One of the applications of annuities in society is a credit financial instrument. In the credit system there are many risks, so this study is to compare the installment system according to the fastest and longest sample periods in credit with the ordinary annuity method system and maturity, in addition this study aims to see the movement of installments using flat interest and effective interest. The calculation results for a loan of Rp 17,915,000, within 11 months with 24% interest show the largest total interest on the flat interest type of Rp3,941,300 and the smallest total interest on the annuity interest due of Rp1,825,879. Meanwhile, the calculation of the second sample with a loan of Rp17,915,000, within 35 months with an interest of 17.32% obtained the largest total interest on the flat interest type of Rp9,050,055, with the smallest total on the effective interest type of Rp4,339,610, but only slightly different from the total interest on the annuity due of Rp4,347,542. From these results, creditors are advised to choose a credit in a period of 11 months with an annuity due, because the interest paid is much smaller than the 35-month period.